Wage Dispersion, Over-Qualification, and Reder Competition - Ekkehart Schlicht (Economics: The Open-Access, Open-Assessment E-Journal, 2007)
The expansion of higher education in the Western countries has been accompanied by a marked widening of wage differentials and increasing over-qualification. While the increase in wage differentials has been attributed to skill-biased technological change that made advanced skills scarce, this explanation does not fit well with the observed increase in over-qualification which suggests that advanced skills are in excess supply. By ?Reder-competition? I refer to the simultaneous adjustment of wage offers and hiring standards in response to changing labor market conditions. I present a simple model of Reder competition that depicts wages as driven by labor heterogeneity, rather than scarcity. The mechanism may give rise to a simultaneous increase in wage differentials and over-qualification.
Keywords: D43; J63; J31; 330; Hiring standards; employment criteria; selection wages; efficiency wages; mobility; skillbiased technological change; heterogeneity-biased technological change; over-qualification; over-education; wage dispersion; Reder competition; Personalbeschaffung; Qualifikation; Lohndifferenzierung; Überqualifikation; Technischer Fortschritt